Sialendoscopy-assisted transfacial surgery for the removal of an iatrogenic foreign body in Stensen's duct: a stone and broken wire basket. Issue 5 (10th February 2016) - Capaccio, P; Gaffuri, M; Torretta, S; Pignataro, L
Abstract: Background: A foreign body is a rare cause of parotid gland obstructive sialadenitis; intra-oral penetration via Stensen's duct is unusual. The relatively recent introduction of interventional sialendoscopy to treat obstructive sialadenitis has allowed surgeons to adopt a gland-sparing approach by means of miniaturised endoscopes and instruments. However, unusual anatomy or pathological conditions can give rise to a risk of intraductal rupture that may lead to a subsequent iatrogenic foreign body. Case report: This paper describes the case of a patient with a 4 mm stone engaged by a broken wire basket stuck in a secondary branch of Stensen's duct. Results: The iatrogenic foreign body was successfully retrieved by means of sialendoscopy-assisted transfacial surgery. Conclusion: This is the first reported case of an intraductal rupture of a miniaturised device during interventional sialendoscopy successfully resolved by means of combined endoscopy and external surgery. This proved to be an effective method of rescuing a foreign body stuck in Stensen's duct.